De Macondo a Medellín: viaje de ida y vuelta - Jastrzębska, Adriana Sara (Romanica Silesiana)
The weight of the figure of Gabriel García Márquez and of magical realism in later generations is the root of a conflict that has become a part of literary matters. The writer’s work has become an inevitable reference for all Colombian writers, no matter how much it is hated, petrifying into a label that is as frequent as it is erroneous. In the writings of such authors as Fernando Vallejo, Héctor Abad Faciolince, Nahum Montt or Juan Gabriel Vásquez, the complex relationship with the heritage of García Márquez is reiterated as a secondary theme, complementing the image of violent Colombia. The article discusses specific examples of narrative works of the above mentioned authors and their very specific, respectful attitude to the paternal figure of García Márquez and his work, to love-and-hate, to rejection-and-tribute, to a simultaneous affirmation-and-negation, which results in an ironic transformation and reinterpretation of the concept of magical realism and of the Macondian heritage, and subsequently widens the perspective from which the literary image of contemporary Colombia is constructed and read. Key words: Magical realism, Colombia, recent literature, Gabriel García Márquez.